Current status of family medicine in Kenya; family physicians' perception of their role - Kaja Momanyi; Geert-Jan Dinant; Marlieke Bouwmans; Simone Jaarsma; Patrick Chege (AOSIS, 2020)
Background: Family medicine (FM) was introduced in Kenya in 2005. Up to date (August 2019), 42 family physicians have graduated from Kenyan Universities. Aim: The aim of the study was to establish the current state of FM in Kenya and identify areas for more research and actions to support and improve FM in Kenya. Setting: Interviews were conducted at the different work sites of the participants, four of them in hospitals, one at a University and one in a hotel where a FM conference was held. Methods: An online questionnaire (response rate = 56%) and six semi-structured interviews were conducted amongst family physicians who completed their studies in Kenya. However, the focus was on the interviews. Results: Family physicians have different ideas of how FM should look like ideally, but all agree that family physicians should be team leaders of a primary healthcare team, taking care of a defined population. Lack of policies, low numbers of family physicians and the misunderstanding of FM by all stakeholders are the major challenges. Sixty-four percent of the participants work in rural areas, and 77% perceive their current work as FM. Conclusion: Family medicine must be defined and properly promoted. Various areas have been identified that require further research: assessing required number of family physicians, reasons and solutions for the low number of family physicians, funding possibilities, and research the most suitable definition of a Kenyan family physician.